Response of foliar application of iron and green manuring in dry direct-seeded and transplanted rice (Oryza sativa) - MAHAJAN, G; SEKHON, N K; SIDHU, A S (The Indian Journal of Agricultural Sciences, 2012)
Deficiency of N and Fe significantly influenced performance of rice, especially on coarse texture soil. The present study leads to the conclusion that grain yield of DSR can be increased by green manuring and foliar application of Fe. Green manuring also resulted in increase in yield of PTR. Green manured DSR plots recorded same yield as PTR plots without green manuring.